Anastomosing hemangioma arising from the kidney: a case of slow progression in four years and review of literature - Zhang, Wei (Int J Clin Exp Pathol, 2015)
Reported herein is a renal anastomosing hemangioma which developed slowly in the past four years. A 25-year-old woman was found a mass localized in the upper portion four years ago, and only slow progression in the past four years. She underwent a laparoscopic partial nephrectomy of right kidney and diagnosed as anastomosing hemangioma. On histology the vascular components of the tumor had an anastomosing pattern without well-definite margins. Immunohistochemically, only endothelial markers (CD31, CD34) were expressed on the vascular components of tumor cells. Smooth muscle actin (SMA), cytokeratin (CK), EMA and S-100 and so on were all negative in the epithelioid tumor cells. The patient was alive at 16 months after operation, without any evidence recurrence or metastasis. Anastomosing hemangioma is an extremely rare vascular neoplasm; only 23 cases were previously described until now. Our report of anastomosing hemangioma arising from the kidney with slow progression will improve the knowledge of primary vascular tumors arising in the kidney.